WRITING FROM SOURCES: PROCESS, PROBLEMS, AND SOLUTIONS - Muhammad Nadjmuddin (Holistics (Hospitality and Linguistics) : Jurnal Ilmiah Bahasa Inggris, 2010)
The competence of writing from multiple sources is crucial for EFL  students in higher education. The academic writing process requires the support and integration of various skills such as fluency as well as the skills  of integrating information from the source texts within the written text, reading  the rhetoric context and intepreting  the task. The aim of  this article is to investigate the writing process from sources in EFL setting. This article discusses the complexity of the writing-form-sources task such as how students construct a task representation and personal and contextual factors that influenced the creation of the participants’ task representations, other factors such as individual background experiences. Language proficiency is assumed affect reading and writing performance. Some suggestions are presented to help teachers designing the task of reading and writing from source texts.